Clinical Features and Prognosis of Uveitis in a Turkish Patient Population with Ankylosing Spondylitis: Incidence and Management of Ocular Complications. (19th May 2019) - Sungur, Gulten; Yakin, Mehmet; Uzman, Selma; Balta, Ozgur; Orman, Gozde; Ornek, Firdevs
ABSTRACT: Purpose : To investigate clinical features, visual prognosis, and ocular complications in patients with ankylosing spondylitis (AS)-associated anterior uveitis (AU). Methods : Data of 211 eyes of 145 patients with AU associated with AS were reviewed retrospectively. Results : Mean follow-up time was 6.31 ± 6.33 years. Men were younger than women at AS diagnosis ( p = 0.035). The mean number of uveitis flares was highest during the first quarter of the year and lowest during the third quarter ( p = 0.017). Immunosuppressive agent use was higher in women than men ( p = 0.052). Ocular complications developed in 120 eyes (56.9%), and the complication rate was 0.146/eye year. Males developed cystoid macular edema more frequently than females ( p = 0.05). Glaucoma was observed more often in early-onset disease (age at AS onset <45 years) than late-onset disease ( p = 0.028). Conclusions : Visual prognosis of AU in patients with AS was good, although more than half of the eyes developed ocular complications (56.9%).